Hubungan Pemberian Makanan Mengandung Kalsium dan Vitamin D Secara Rutin oleh Ibu dengan Kejadian Stunting pada Balita di Kabupaten Sijunjung–Sumatera Barat - Cindy Elvionita; Cindy Elvionita (LPPM Universitas Abdurrab, 2023)
Stunting is a disruption in the growth and development of children within 1000 days of life due to chronic malnutrition and recurrent infections which is characterized by their length or height being below standard. Calcium and vitamin D are nutrients that influence bone mineralization. Good bone mineralization during growth allows optimal linear growth. This study aims to determine the relationship between providing food containing calcium and Vitamin D with the incidence of stunting in children under five in Sijunjung Regency. This research is a quantitative research with an analytical observational design with a cross sectional approach method. The number of samples in this study was 36 people with a distribution of 13 men (35.71%) and 23 women (64.29%). There were 5 (38.46%) male toddlers and 9 (39.13%) female toddlers who experienced stunting. Based on data analysis carried out using chi-aquare (X2), it was found that p=0.021 and p=0.018 for the relationship between calcium and vitamin D intake and the incidence of stunting. Based on this, it shows that p < 0.05. Based on the research results, it can be concluded that there is a significant relationship between providing food containing calcium and vitamin D and the incidence of stunting in toddlers in Sijunjung Regency.